The effectiveness of the PDEODE strategy in the reflective thinking of fifth-grade literary students and the development of their motivation towards geography - سعيد جاسم مرتضى (Journal of College of Education, 2023)
The aim of the research is to identify the effectiveness of PDEODE strategy in reflective thinking among fifth-grade literary students and develop their motivation towards geography, by verifying micro-hypotheses. . The research community was determined by students of the fifth literary grade in middle schools for boys in Al-Rifai District of Dhi Qar Governorate, and the number of the community reached (376) students. The Allama Preparatory School for Boys was chosen by random assignment to represent the research sample, and Division (A) was chosen by random assignment to be the experimental group, and the number of students in it was (23) students. Students (24) students, and the same habit is taught according to the usual method. The researcher adopted the following statistical methods: the second test for two independent samples, the Facronbach equation, the Kapuder-Richardson equation 20, the Pearson correlation coefficient. The research tools consisted of: the reflective thinking test. The researcher built and prepared the choice of reflective thinking, which includes (25) items, and the learning motivation scale. The researcher built and prepared the learning motivation scale, which consists of (24) items. The following: 1- There is a statistically significant difference between the experimental and control groups in the reflective thinking variable in favor of the experimental group. 2- There is a statistically significant difference between the experimental and control groups in the learning motivation variable in favor of the experimental group. In light of these results, the researcher concluded that the adoption of the PDEODE strategy had a significant and positive impact on improving the contemplative thinking and learning motivation for students of the fifth Prophet. The researcher also recommended applying this strategy to other social subjects because of their key role in teaching